(untitled) (Comprehensive Journal of Science, 2026)
In recent decades, the world has witnessed a significant increase in the scale and severity of environmental damage affecting both terrestrial and marine environments. This is due to transnational industrial and economic activities, coupled with weak monitoring and rescue mechanisms in many countries. As a result, environmental crime has emerged as one of the most significant challenges to contemporary criminal policy, with direct repercussions for human health, food security, biodiversity, and sustainable development. This research aims to study the legal framework governing environmental crime, both on land and at sea, by analyzing relevant international environmental law rules and comparing them with Libyan national environmental legislation, particularly Law No. 15 of 2003 on the Protection and Improvement of the Environment, Law No. 8 of 1973 on the Prevention of Oil Pollution of Sea Water, Law No. 14 of 1989 on the Exploitation of Marine Resources, and laws regulating forests, rangelands, wildlife, and agricultural lands. The research stems from a central problem addressed in the following question: To what extent do international environmental law and Libyan national law provide an effective framework for criminalizing environmental crimes in terrestrial and marine environments, and what are the points of convergence and divergence between them in terms of criminalization, punishment, and rescue mechanisms? The study adopted a comparative analytical approach, examining key relevant international agreements, analyzing Libyan legal texts, and comparing them in light of international standards. It concluded that the Libyan legislative environment, in its broad outlines, aligns with international trends in environmental protection and the criminalization of harmful acts. However, the challenges of implementation, weak institutional capacity, and the need to update certain texts to keep pace with international developments (particularly in the areas of hazardous waste and transnational environmental crimes) remain significant shortcomings requiring attention.